STRATEGI PENINGKATAN PROFIT USAHA RITEL PADA PONDOK PESANTREN - Moh Rifa'i (Nurul Jadid University, 2020)
Increasing retail business profit is the main goal in trading business management. The implication is to contribute to the welfare and development of other retail businesses. However, not all managers can focus on increasing profits for the retail businesses they manage. Many of these efforts are just running away but have not met the required targets, due to various reasons that have developed. Of course, in this case it is necessary to find a solution by learning through research in order to find effective and efficient strategies to do in increasing retail business profits.This study aims to describe the strategy to increase retail business profit at MJ Swalayan at Al-Mashduqiah Kraksaan Islamic Boarding School, Probolinggo. The research approach is qualitative with the type of case study. Using in-depth interviews, participant observation, and documentation as data collection techniques. While the data analysis technique applied is the Miles and Huberman model using data reduction, data presentation, drawing conclusions and data verification. By testing the validity of the data through credibility with the source triangulation technique.The results show that in order to increase retail business profit, MJ Swalayan management uses the following strategies; recruitment and selection of Professional HR, implementing SOP (Standard Operating Procedure) for retail services, implementing controlling, ideal merchandising, completing merchandise, establishing cooperation, implementing automatic retail and wholesale pricing systems, implementing low pricing determination, FGC (Focus Group Discussion) on a regular basis , and direct response and problem solving.